Interactive Effects of Nutrition Modification and Wet Cupping on Male Patients with Refractory Stable Angina - Mohammad Abazari; Mahdi Yousefi; Vafa Baradaran Rahimi; Hamideh Vahid; Azadeh Saki; Arash Gholoobi (Korean Pharmacopuncture Institute, 2022)
Objectives: Routine therapies cannot control refractory stable angina, leading to a high economic burden and an impaired quality of life. Persian medicine incorporates exceptional attention to lifestyle and nutrition to prevent and treat various diseases. Previous studies have reported the analgesic and anti-inflammatory effects of wet cupping. The present study aims to determine the effects of nutrition and cupping on refractory stable angina patients.Methods : Forty male patients with refractory stable angina were randomly allocated to four groups, including nutrition modification based on Persian medicine, wet cupping, nutrition modification along with wet cupping, and control. The primary outcomes were the changes in pain score using a visual analog scale and quality of life using the Seattle angina questionnaire. The secondary outcomes were changes in the exercise test and blood pressure.Results : The results of the present study revealed that 30 days of treatment with nutrition modification based on Persian medicine, cupping, and modified nutrition and cupping along with standard treatment for stable angina significantly increased the patient's quality of life and exercise test results while reducing pain, and systolic and diastolic blood pressure.Conclusion : Applying complementary Persian medicine methods such as nutrition modification and cupping along with the classical medical treatments may improve outcomes for refractory stable angina patients.